Mecanismos de hipertrofia muscular induzida pelo treinamento de força: análise de marcadores de proteólise, remodelamento de matriz extracelular e adição de mionúcleos mediada por células satélite - Scarpelli, Maíra Camargo (2024)
The increase in muscle mass (i.e., muscle hypertrophy) promoted by resistance training (RT) results from the activation and coordination of various molecular mechanisms. Some of them have been widely examined, such as satellite cells and the addition of myonuclei to muscle fibers. On the other hand, other mechanisms, such as the activity of enzymes that regulate proteolysis and extracellular matrix (ECM) remodeling, have been poorly investigated. Considering that increased muscle mass positively impacts health and well-being, it seems imperative to investigate the effect of RT on these mechanisms, as well as to explore strategies to optimize individual hypertrophic responses, for example, through RT overload progression. Thus, this study aims to investigate whether: (1) individual muscle hypertrophy responses to different overload progression protocols can be explained by changes in total myonuclei and satellite cells content or changes in the protein content and enzymatic activity levels of proteolytic biomarkers and ECM remodeling factors; (2) acute responses of protein content and enzymatic activity levels of proteolytic biomarkers and ECM remodeling factors to an RT bout performed in the trained state are attenuated compared to responses to a naïve bout (i.e., performed in the untrained state). The results indicate that: (1) individual prescription of overload progression can improve intra-subject responsiveness to RT; however, the greater responsiveness to one protocol or another is not explained by the investigated molecular mechanisms; (2) biomarker responses are not attenuated in the trained state compared to responses observed in the untrained state, suggesting that proteolysis and ECM remodeling responses are likely sustained to promote muscle hypertrophy and remodeling.